On the foundation of thermal "Switching": The culture substrate governs the phase transition mechanism of thermoresponsive brushes and their performance in cell sheet fabrication. (December 2021) - Stöbener, Daniel D.; Weinhart, Marie
Abstract: Thermally "switchable" poly(glycidyl ether) (PGE) brushes constitute effective coatings for the temperature-triggered harvest of confluent cell sheets. Based on a simple "grafting-to" approach, such coatings can be tethered to various applied plastic culture substrate materials. Herein, we elucidate the self-assembly of PGE brushes with tunable grafting densities up to 0.12 and 0.22 chains nm −2 on polystyrene (PS) and tissue culture PS (TCPS), respectively. In terms of temperature-dependent wettability and protein adsorption, we found that brushes exhibit distinct grafting density-dependent properties which correlate with their cell sheet fabrication performance. In addition, temperature-ramped quartz-crystal microbalance with dissipation (QCM-D) measurements revealed marked substrate-specific PGE phase transitions which allowed us to deduce comprehensive switching mechanisms. Thus, we demonstrate that brushes tethered to hydrophilic TCPS (contact angle (CA) ∼ 60°) undergo a "cushioned" transition comprising a non-switchable, hydrated basal layer as well as a switchable top layer which regulates cell sheet detachment. In contrast, PGE brushes tethered to PS undergo a "grounded" transition which is substantially influenced by the dehydrating effect of the less hydrophilic PS substrate (CA ∼ 90°). These divergent phase transition mechanisms give rise to a broad scope in cell sheet fabrication performance, yielding staggered detachment times within a 30 min to 3 h range. Hence, we emphasize the importance of a detailed knowledge on the effect of applied culture substrates on the thermal switchability and phase transition characteristics of thermoresponsive brush coatings to accomplish an optimized design for functional cell culture dishes. Statement of significance: As the first comparative study of its kind, we elucidate the substrate-dependent thermal switchability of thermoresponsive brush coatings and evaluate their grafting density-dependent phase transition mechanism and its effect on cell sheet fabrication performance. Graphical abstract: Image, graphical abstract